Effect of stocking rate on the botanical composition and nutritive value of diets selected by West African Dwarf goats maintained on researcher-managed and farmer-managed stylo fodder banks during the cropping season in central Nigeria - Njwe, R.M.; Ikwuegbu, O.A.; Tarawali, G.; Little, D.A. (Elsevier, 1995)
In Nigeria, researcher-managed and farmer-managed West African Dwarf goats were grazed on Stylosanthes hamata (stylo) fodder banks at stocking rates of 29, 43 and 57 goats/ha and 22-25, 42-43, 50-55 and 68-92 goats/ha, respectively. Extrusa samples were taken from oesophageally fistulated goats to determine the selectivity index, botanical composition, nutritive quality of diet and DM degradability. Irrespective of stocking rate, goats in both trials selected more stylo than grass. In the researcher-managed trial the proportion of stylo in the diet increased with increasing stocking rate (55.3 and 75.7 percent at 29 and 57 goats/ha, respectively). Increasing the stocking rate from low (22-25 goats/ha) to medium (42-43 goats/ha) in the farmer-managed trial resulted in an increase in stylo proportion in the diet from 79.2 to 87.7 percent; further increases in stocking rate resulted in a decrease in proportion of stylo in the diet (56.8 percent at 68-92 goats/ha). The percentage of DM degraded in the rumen was highest at 56 and 46 days of grazing in researcher-managed and farmer-manager trials (74.6 and 77.8 percent, respectively) and at medium stocking rates (43 and 42-43 goats/ha) for both (75.1 and 78.6 percent for researcher-managed and farmer-managed, respectively). The CP content of diets decreased as the time spent grazing increased. An increase in stocking rate did not affect the CP or NDF content of the goats diets. Calcium and magnesium levels in the diets were sufficient to meet the requirements of goats.